Effect of procyanidin on dietary iron absorption in hereditary hemochromatosis and in dysmetabolic iron overload syndrome: A crossover double-blind randomized controlled trial. Issue 1 (January 2020) - Lobbes, Hervé; Gladine, Cécile; Mazur, Andrzej; Pereira, Bruno; Dualé, Christian; Cardot, Jean-Michel; Ruivard, Marc
Summary: Background & aims: Type I hereditary hemochromatosis (HH) and dysmetabolic iron overload syndrome (DIOS) are the two most prevalent iron overload diseases. Although many food components, particularly polyphenols, reduce iron bioavailability, there is no clinically validated nutritional strategy to reduce food-iron absorption in patients with these diseases. We aimed to determine whether supplementation with 100 mg of procyanidins during a meal reduces dietary iron absorption in patients with HH or DIOS. Methods: 20 HH and 20 DIOS patients were enrolled in a double-blind three-period crossover randomized study. Basal serum iron level was measured following an overnight fast. Each patient consumed a standardized test iron-rich meal containing 43 mg of iron with two capsules of placebo or procyanidin supplementation. Each period was separated by a 3-day wash-out period. The primary objective was a reduction of dietary iron absorption, assessed by a reduction of serum-iron area under the curve (AUC) corrected for baseline serum iron. Results: All patients completed the study. The meal and the procyanidin supplements were well tolerated. In both HH and DIOS patients, the iron-rich meal induced a significant increase of serum iron compared with baseline at 120, 180, 240 min, from 8 to 9.1% (p = 0.002, 0.001 and 0.003, respectively) in DIOS and from 15.8 to 25.7% (p < 0.001) in HH. Iron absorption was 3.5-fold higher in HH than in DIOS (p < 0.001). Procyanidin supplementation did not significantly modify iron absorption in DIOS (AUC of added iron 332.87 ± 649.55 vs 312.61 ± 678.61 μmol.h/L, p = 0.916) or in HH (1168.62 ± 652.87 vs 1148.54 μmol.h/L ± 1290.05, p = 0.917). Conclusions: An iron-rich test meal led to a marked increase in iron absorption in HH but a mild increase in DIOS. Procyanidin supplementation does not significantly reduce dietary iron absorption in either disease. Clinical trial registry: clinicaltrials.gov (NCT03453918 ).